Substrate Effects on Charge Carrier Transport Properties of Single‐Crystal CVD Diamonds and an 8 mm Square Radiation Energy Spectrometer. Issue 22 (14th November 2018) - Hirano, Shintaro; Kaneko, Junichi H.; Hanada, Takanori; Ito, Shogo; Shimaoka, Takehiro; Shimmyo, Hiroaki; Tsubota, Masakatsu; Chayahara, Akiyoshi; Mokuno, Yoshiaki; Umezawa, Hitoshi
Abstract : In an effort to enlarge a sensitive area of a diamond radiation energy spectrometer, a self‐standing chemical vapor deposition (CVD) single crystal is grown on an 8‐mm‐square "general grade" CVD single‐crystal diamond substrate fabricated by Element Six Ltd. The growth conditions that achieved a μτ product of 3 × 10 −4  cm 2  V −1 for holes in a CVD single‐crystal diamond grown on a high‐pressure and high‐temperature (HP/HT) type IIa single‐crystal diamond substrate elsewhere are adopted. The charge collection efficiency (CCE) of 99.9% for both charge carriers, and 0.39% and 0.5% of energy resolution for holes and electrons are achieved using 5.486 MeV alpha particles. Uniformity of the energy resolution is sufficient for the use of a radiation energy spectrometer. However, μτ products of (5.0 ± 0.4) × 10 −5 and (1.8 ± 0.2) × 10 −5  cm 2  V −1 for holes and electrons are obtained, respectively. These values are approximately one order of magnitude smaller than the μτ products of the CVD single crystal grown on a HP/HT type IIa diamond substrate using the same growth conditions. Abstract : A diamond energy spectrometer is fabricated by a self‐standing CVD single‐crystal diamond grown on a 8 mm square "general grade" CVD single‐crystal diamond substrate fabricated by Element Six Ltd. The charge collection efficiency (CCE) of 99.9% for both charge carriers, and 0.39% and 0.5% of energy resolution for holes and electrons are achieved using 5.486 MeV alpha particles.